The carcinological oeuvre of Charles Spence Bate (1819–1889): Checklist of species and genera, dates of publication, and a list of publications (Crustacea: Amphipoda, Cirripedia, Cumacea, Decapoda, Tanaidacea) - De Grave, S; Boyko, CB (Oxford University Press, 2024)
Charles Spence Bate (1818–1889) was one of the more influential mid to late 19th century crustacean taxonomists, with broad interests spanning several taxonomic groups, such as Amphipoda and Decapoda. Despite several contemporary obituaries, no full publication list for him has ever been assembled. In the present contribution, we provide a complete listing of publications and all species- and genus-level crustacean taxa described by Spence Bate, and indicate their current status. Corrections to publication dates are listed, and several decisions are made to stabilise crustacean nomenclature. In a scientific career spanning almost 50 years (1850–1889), Spence Bate described a total of 402 species and 70 genera in Decapoda, 181 species and 46 genera in Amphipoda, as well as eight genera and eight species of Cumacea, four genera and 16 species of Isopoda, three of Tanaidacea and one of Cirripedia. Of these, 36.2% of species and 45.7% of genera are still considered as the accepted names for their taxa today.